2022
DOI: 10.3389/fpsyg.2022.705442
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Approach to Analyzing the Effects of Stress on Individual Creativity in Business Problem-Solving: Emphasis on the Electrocardiogram, Electroencephalogram Methodology

Abstract: In this study, experiments were conducted on 30 subjects by means of electrocardiogram (ECG) and electroencephalogram (EEG) methodologies as well as a money game to examine the effects of stress on creativity in business problem-solving. The study explained the relationship between creativity and human physiological response using the biopsychosocial model of challenge and threat. The subjects were asked to perform a cognitive mapping task. Based on the brain wave theory, we identified the types of brain waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 135 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…Fink and Benedek [40] showed that the alpha band is systematically activated during creative tasks: the more a task is creativity-related, such as finding original alternate solutions to a problem, the stronger is the synchronization of alpha activity. Also, alpha waves increased in the frontal lobe of the brain during creative business problem-solving but decreased under stressful conditions, during which beta waves in the brain increased [41].…”
Section: A Neuroscientific Approach To Measure Group Creativitymentioning
confidence: 96%
See 1 more Smart Citation
“…Fink and Benedek [40] showed that the alpha band is systematically activated during creative tasks: the more a task is creativity-related, such as finding original alternate solutions to a problem, the stronger is the synchronization of alpha activity. Also, alpha waves increased in the frontal lobe of the brain during creative business problem-solving but decreased under stressful conditions, during which beta waves in the brain increased [41].…”
Section: A Neuroscientific Approach To Measure Group Creativitymentioning
confidence: 96%
“…Previous studies exploited the analysis of EEG frequency bands (namely, delta, theta, alpha, and beta waves), and their functional meaning according to the process of interest and their neural localization, to elucidate the role of specific cortical areas supporting the creative process [37,40,41]. For instance, in the context of creativity, an increase in the low frequency band (delta and theta band) in the frontal regions was previously associated with the process of creative insight and integration of new information coupled with an affective orientation towards satisfaction [42].…”
Section: A Neuroscientific Approach To Measure Group Creativitymentioning
confidence: 99%
“…Recent studies have aimed to objectively quantify mental stress by analyzing physiological responses to stress using wearable sensors (4)(5)(6). Lee et al (4) measured Electrocardiogram (ECG) and Electroencephalogram (EEG) data while the participants played money games, and they analyzed the effects of stress on human physiological response.…”
Section: Introductionmentioning
confidence: 99%